Satisfaction of basic psychological needs and European entrepreneurs' well-being and health: The association with job satisfaction and entrepreneurial motivation. - Padilla-Angulo, Laura; Lucía-Casademunt, Ana María; Gómez-Baya, Diego (Wiley, 2023)
Purpose: We examine an integrative model associating entrepreneurial motivation and job satisfaction with basic psychological needs satisfaction and the psychological well-being (PSW) and health problems of European entrepreneurs. In contrast with previous literature that mainly focuses on hedonic well-being, this study examines eudaimonic well-being and the link between entrepreneurial motivation and entrepreneurs' PWB. Design/methodology/approach: Based on the Self-Determination Theory (SDT) and using structural equation modelling, this study examines a European representative sample composed of 7878 entrepreneurs from the sixth “European Survey on Working Conditions” (6th EWCS; Eurofound, 2015 database) Findings: This study finds a positive relationship between the satisfaction of the need for autonomy and competence and opportunity motivation, which in turn is positively associated with job satisfaction. This study also finds that need satisfaction is positively associated with entrepreneurs' PWB and job satisfaction, which in turn is positively associated with entrepreneurs’ PWB and health. Results highlight the relevance of SDT, opportunity motivation, and job satisfaction to understanding entrepreneurs' PWB and health. Originality: To the best of our knowledge, this is the first integrative model relating satisfaction of basic psychological needs (autonomy and competence) and diverse individual outcomes related to work (job satisfaction, PWB, and health) of European entrepreneurs, by considering entrepreneurial motivation. This study examines a large and representative European sample, in contrast with previous research focusing on the Anglosphere nations.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/3792?template=romeo
Keywords: Empresarios - Psicología; Trabajo - Aspectos psicológicos; Entrepreneurs’ health; Need satisfaction; Opportunity motivation; Self-determination theory.; Entrepreneurs’ psychological well-being